(untitled) (Research, Society and Development, 2025)
Over the years, allogeneic blood transfusion has become one of the most common medical practices worldwide. Over the years, allogeneic blood transfusion has become one of the most common medical practices worldwide. Unfortunately, it has often been prescribed in a deliberate and unnecessary manner. Transfusions carry risks and increase costs, and should only be used when clinically indicated. The aim of the present study was to clarify, through a narrative review, the potential positive effects that Patient Blood Management (PBM) can bring to healthcare economics, whether in the private or public sector. Thus, it is divided into three pillars: preoperative, intraoperative, and postoperative. PBM demonstrates economically significant outcomes by effectively reducing overall hospital costs and those related to blood transfusions, decreasing length of stay, and improving patient safety. Therefore, the present study aimed to clarify the potential positive effects that PBM can bring to healthcare economics by gathering data from the PubMed and LILACS databases.